Propagation and dissipation of typhoon-induced surface waves along the Pearl River Estuary - Liang, Mingen; Zhu, Suijie; Qiu, Heyong; Jia, Liangwen (Frontiers in Marine Science, 2024)
The propagation and dissipation of typhoon-induced surface waves are vital to morphological evolution and related engineering within coastal and estuarine regions. An observation system was operated during Typhoon Higos, and TELEMAC–TOMAWAC numerical modeling was performed for Typhoons Hagupit, Hato, and Higos along the central coast of Guangdong and the Pearl River Estuary in China to explore variations in wave propagation and dissipation during typhoons. The results showed that wind waves were dominant before typhoon landfall, and the intense wind waves dissipated rapidly during typhoon decay, while they could stay longer within the estuarine regions. Landward wave propagation had a tendency to convert from being convergence-dominated to being dissipation-dominated with the morphological change and tended to converge at the mouth-bar region. Within the estuarine regions, waves dissipated more rapidly at the prismatic estuary than at the bell-shaped bays due to the limited width and rapid contraction of the outlet. Moreover, the track and scale of typhoons had critical effects on the generated wave field, and they dominated the intensity, propagation, and dissipation of the overall wave field. Specifically, typhoons with broader scales and longer moving tracks within the coastal regions of Guangdong Province enhanced the wind–wave interaction and induced a stronger and wider wave field, despite that their typhoon intensities were comparable (i.e., Hagupit vs. Hato). Furthermore, waves generated by compact and regular cyclone structures dissipated more strongly along the moving track of typhoons (i.e., Hato and Higos). Except for typhoons directly attacking the Pearl River Estuary, waves within the estuarine regions tended to dissipate/converge when located on the right/left side of the moving track of typhoons.